Coping a young woman's guide to breast cancer prevention - Eisenpreis, Bettijane (New York Rosen Pub. Group, 1999)
A guide to understanding breast cancer, its cause, and its treatment.
Keywords: Breast -- Cancer -- Juvenile literature